2021
DOI: 10.3390/agronomy11081472
|View full text |Cite
|
Sign up to set email alerts
|

Can Long-Term Experiments Predict Real Field N and P Balance and System Sustainability? Results from Maize, Winter Wheat, and Soybean Trials Using Mineral and Organic Fertilisers

Abstract: Agri-environmental indicators such as nutrient balance may play a key role in soil and water quality monitoring, although short-term experiments might be unable to capture the sustainability of cropping systems. Therefore, the objectives of this study are: (i) to evaluate the reliability of long-term experimental N and P balance estimates to predict real field (RF) (i.e., short-term transitory) conditions; and (ii) to compare the sustainability of short- and long-term experiments. The LTE-based predictions sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…The temperate Himalayan regions of Pakistan and India have witnessed rapidly decreasing soil fertility over time leading to decline in crop productivity [6,8]. It needs emphasis that for ensuring food security, healthy soils form the foundation of food production, conservation of water and biodiversity especially bacterial community in the rhizosphere and nutrient cycling in agricultural eco-systems [9]. Recently, soil health (soil potential as a living system for sustaining plant and animal productivity along with maintaining water and air quality) and environmental pollution caused by excessive use of chemical fertilizers have received due attention [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperate Himalayan regions of Pakistan and India have witnessed rapidly decreasing soil fertility over time leading to decline in crop productivity [6,8]. It needs emphasis that for ensuring food security, healthy soils form the foundation of food production, conservation of water and biodiversity especially bacterial community in the rhizosphere and nutrient cycling in agricultural eco-systems [9]. Recently, soil health (soil potential as a living system for sustaining plant and animal productivity along with maintaining water and air quality) and environmental pollution caused by excessive use of chemical fertilizers have received due attention [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Being a leguminous crop, soybean plants primarily meet their nitrogen (N) requirement from symbiotic fixation (BNF) process, however, a number of field studies have reported contradictory findings regarding the impact of organic manures on soybean yield [7,9,23]. Schmidt et al [24] inferred that soybean yield was enhanced by 1.4 kg per kg of applied N in the form of well-composted organic manures especially chicken manure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, crops are very efficient, with the P they use showing high efficiencies; thus, reinforcing the fact that they do not respond to increases in added P beyond their inherent critical requirements [84]. This paper, along with the recent work of Piccoli [85] are, thus far, the only known attempts to devise (in graphic form) the critical P input-output levels in order to minimize P surpluses in croplands that receive fertilizer or manure.…”
Section: Determining Safe Levels Of P Loading From Manurementioning
confidence: 99%
“…Agri-environmental indicators are particularly widespread [21]. One example of their use is to calculate a nutrient balance using nutrient inputs and outputs [22], for example to monitor fertiliser policies. These indicators are in contrast to use indicators, which do not capture productivity or environment-related effects [19,23].…”
Section: Of 21mentioning
confidence: 99%